Pengaruh Pembagian Kerja Terhadap Efektivitas Kerja Karyawanbagian Operasional Pada PT.Rinjani Kartanegara Di Desa Bakungan - Palinggi, Yonathan (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2015)
PT. Rinjani mammal is one of the companies in Kutai regency engaged in coal company with Manager Mr Bhondan Soeryo as for the study was conducted on the operational part of the PT. Rinjani mammal which is located Jln. Dayaku gate Village Subdistrict Bakungan Loa Janan RT. 10. The number of existing employees in the Operations Section at PT. Rinjani Kartanegara Loa Village Hyacinths Loa Janan subdistrict totaled 179 employees and operates in the village Bakungan Kukar. The purpose of this study was to determine the amount of variable division of labor Against Employee Effectiveness of Operations at PT. Rinjani Kartanegara In the village Bakungan and to answer the truth of the hypothesis that has been proposed investigators. The analytical tool used in this research is simple regression method with SPSS 21.0 For Windows, with a population of 179 respondents an. From the research results can be concluded that it is indeed a significant difference between the variable division of labor on the operational part of the effectiveness of employees at PT. Rinjani Kartanegara Regency. Thus the hypothesis proposed in this study is: